2015
DOI: 10.1016/j.ijsolstr.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

3D finite element simulations of high velocity projectile impact

Abstract: Abstract. An explicit three-dimensional (3D) finite element (FE) code is developed for the simulation of high velocity impact and fragmentation events. The rate sensitive microplane material model, which accounts for large deformations and rate effects, is used as a constitutive law. In the code large deformation frictional contact is treated by forward incremental Lagrange multiplier method. To handle highly distorted and damaged elements the approach based on the element deletion is employed. The code is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, for structures subjected to very high strain rates (>10 s -1 ), e.g. high-speed projectiles impact on concrete slabs, it has in [53] been shown that the bulk viscosity can have a significant influence on the resulting projectile penetration depth. There, it is also argued that bulk viscosity, due to both physical aspects and numerical reasons, must be included in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, for structures subjected to very high strain rates (>10 s -1 ), e.g. high-speed projectiles impact on concrete slabs, it has in [53] been shown that the bulk viscosity can have a significant influence on the resulting projectile penetration depth. There, it is also argued that bulk viscosity, due to both physical aspects and numerical reasons, must be included in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of loading rate on the behavior of quasi-brittle materials and structures has been intensively studied and better understood in recent years [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. It is well known that the resistance, failure mode, crack pattern and crack velocity in concrete are strongly influenced by the loading rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the resistance, failure mode, crack pattern and crack velocity in concrete are strongly influenced by the loading rate. The rate dependent response of concrete is controlled through three different effects: (i) through the rate dependency of the growing micro-cracks (inertia effects at the micro material level); (ii) through the viscous behavior of the bulk material between the cracks (viscosity due to the water content) and (iii) through the influence of inertia on a meso and macro scale, which comes from different sources [ 27 , 28 , 29 , 30 , 31 ]. In numerical studies (meso- or macro-scale), the first two effects should be accounted for through the constitutive law and, assuming that the resolution of structural discretization is fine enough, the third effect should be automatically accounted for through dynamic analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quasi-brittle materials, such as concrete, the first two effects are important for relatively low and medium strain rates. For higher strain rates (impact) the influence of inertia dominates, however, the rate dependency cannot be neglected [13].…”
Section: Introductionmentioning
confidence: 99%